2008
DOI: 10.1677/erc-08-0116
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in Japanese prostate cancer patients under androgen-deprivation therapy

Abstract: Androgen-deprivation therapy (ADT) of patients with prostate cancer (PCa) is known to reduce bone mineral density (BMD). However, the most studies examined Caucasian or black patients and the effects of ADT on the bone metabolism of East Asians are unclear. Therefore, we performed a crosssectional study to elucidate the influence of ADT on bone metabolism in Japanese patients. In total, 101 native Japanese patients with PCa were enrolled. They consisted of 58 ADT-treated and 43 hormone-naive patients. The BMD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Hussain et al [22] reported that 42% were osteoporotic in a cohort of 176 patients, whereas Morote et al [13] showed an osteoporosis rate of 35.4% in a cohort of 124 patients. Finally, Wang et al [23] reported that 2.3% had osteoporosis among a cohort of 46 ADT-naïve patients. The variation in prevalence of osteoporosis regarding the two first studies is partly caused by the change in consensus of the definition of osteoporosis; both used the old WHO definition, from before 2005, in which both Ward's area and the greater trochanter were included as separate areas, which often resulted in a higher prevalence of osteoporosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hussain et al [22] reported that 42% were osteoporotic in a cohort of 176 patients, whereas Morote et al [13] showed an osteoporosis rate of 35.4% in a cohort of 124 patients. Finally, Wang et al [23] reported that 2.3% had osteoporosis among a cohort of 46 ADT-naïve patients. The variation in prevalence of osteoporosis regarding the two first studies is partly caused by the change in consensus of the definition of osteoporosis; both used the old WHO definition, from before 2005, in which both Ward's area and the greater trochanter were included as separate areas, which often resulted in a higher prevalence of osteoporosis.…”
Section: Discussionmentioning
confidence: 98%
“…The age of the hormone-naïve patients in Morote et al [13] was not reported. Regarding the study by Wang et al [23], the cohort was small and included a Japanese population, which may explain the low prevalence of osteoporosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…African Americans older than 65 years have significantly higher BMD with a similar decline in BMD as compared to Caucasians2425, which may explain the reduced incidence of hip fracture in African Americans, as compared to Caucasians25; whereas, another study on Jamaican men showed ADT with lower BMD26. Some different cross-sectional Asian studies reported that Short-term ADT of an average 23.5 months did not increase the risk of osteoporosis in Japanese prostate cancer patients and ADT was not a significant risk factor for decreased BMD2728. Japanese men exposed to ADT have lower rates of osteoporosis with 2.3% and 8.6% in the hormone-naïve and ADT-treated patients, respectively, which was not statistically significant (p = 0.294).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from the same Japanese research group investigated the effects of ADT on bone mineral density in ADT-treated and hormone-naïve Japanese men. The first study is a cross-sectional study which included 58 ADT-treated and 43 hormone-naïve Japanese prostate cancer patients [22]. The differences in bone mineral density values measured at the lumbar spine, total hip and femoral neck between the two groups of patients did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%